Savagism and civilization : a study of the Indian and the American mind - Pearce, Roy Harvey; Pearce, Roy Harvey (Berkeley : University of California Press, 1988)
First published in 1953, revised in 1964, and presented here with a new foreword by Arnold Krupat and new postscript by the author, Roy Harvey Pearce's Savagism and Civilization is a classic in the genre of history of ideas. Examining the political pamphlets, missionaries' reports, anthropologists' accounts, and the drama, poetry, and novels of the 18th and early 19th centuries, Professor Pearce traces the conflict between the idea of the noble savage and the will to Christianize the heathen and appropriate their land, which ended with the near extermination of Native American culure.
Frontmatter -- Contents -- Foreword / Krupat, Arnold -- Preface -- Part 1: Antecedents And Origins, 1609-1777 -- I. Spirituals And Temporals: The Indian In Colonial Civilization -- Part 2: The Life And Death Of The American Savage, 1777-1851 -- II. A Melancholy Fact: The Indian In American Life -- III. Character And Circumstance: The Idea Of Savagism -- IV. The Zero Of Human Society: The Idea Of The Savage -- V. An Impassable Gulf: The Social And Historical Image -- VI. The Virtues Of Nature: The Image In Drama And Poetry -- VII. Red Gifts And White: The Image In Fiction -- Part 3: Afterthoughts, 1851- -- VIII. After A Century Of Dishonor: The Idea Of Civilization -- Postscript -- Index
Revised edition of: The Savages of America. 1953.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Indians of North America -- Cultural assimilation; Indians in literature; Indians of North America -- Public opinion; Public opinion -- United States; Opinion publique -- États-Unis.; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; HISTORY -- Native American; Indians in literature; Indians of North America -- Cultural assimilation; Indians of North America -- Public opinion; Public opinion; United States; Cultuur; Indianen; Bekering; Assimilatie (sociologie); Noord-Amerika.